دراسة الفعالية المضادّة للفطريات لخلاصات مختلفة للفطر Lactarius sp. تجاه بعض الفطريّات الممرضة - يازجي ميساء; سعود راميا (Latakia University Journal -Biological Sciences Series, 2019)
تم اختبار الفعالية المضادة للخلاصات الإيتانولية والميتانولية والمائية للنوع .Lactarius sp تجاه الأنواع الفطرية المجهرية الممرضة الآتية: ( Trichophyton mentagrophytes,T.rubrum, Epidermophyton floccosum, Fusarium oxysporum, Botrytis cinerea, Aspergillus niger,Candida albicans ). بينت نتائج البحث أنّ الخلاصتين الميتانولية والايتانولية ذات فعالية تثبيطية عالية تجاه معظم الفطريات المختبرة، بينما كانت الخلاصة المائية أقلّ الخلاصات فعالية. أثرت الخلاصات الثلاث في تثبيط نمّو النوع Trichophyton mentagrophytes بشكل واضح ، وبالتركيز (8 mg / ml) وبأقطار تثبيط تراوحت بين (3-20mm)، بينما ثبطت الخلاصتين الإيتانولية والميتانولية فقط نموّ النوعين Aspergillus niger , Botrytis Cinerea ، وكانت جميع الأنواع الأخرى المختبرة مقاومة لجميع الخلاصات، كما اختلفت الخلاصات الثلاث بتناقص أو فقدان فعاليتها بعد المعاملة بدرجتي الحرارة و. In this study, we have tested the effectiveness of three extracts (Ethanol, Methanol, aqueous) of Mushroom, Lactarius sp. against the following pathogenic microfungi (Trichophyton mentagrophytes,T.rubrum, Epidermophyton floccosum, Fusarium oxysporum ,Botrytis cinerea, Aspergillus niger, Candida albicans).The results show that Methanolic and ethanolic extracts have a higher inhibitory effectiveness against most of the tested fungi, while the aqueous extract is the least effective of all. The three extracts have clearly trigerred inhibiting the growth of such a species as Trichophyton mentagrophytes; in concentration (8 mg/ml) with inhibitory diameters ranging between 3 and 20mm, While the Ethanolic and Methanolic extracts have inhibited only the species Aspergillus niger and Botrytis cinerea; all other tested species have resisted all the extracts. The three extracts differ in the decrease or loss of their effectiveness after being exposed to temperatures ranging between () and ().